(untitled) (Baghdad Science Journal, 2016)
A niger, a fungus which doesn’t have high ability to production lipid, this fungus has been select to investigate the non oleaginicity. In this search, there are explorations about: i) growth profile ii) enzymes profile iii) isoforms. Growth profile shows that this fungus doesn’t have ability to accumulate lipid more than 6% while bio mass are around 10g/l in spite of the presence of glucose in the media till the end of cultivation time and excision of nitrogen within 24 hrs. In enzyme study, we investigate all lipogenic enzymes Malic enzyme (ME), Fatty acid synthase (FAS), ATP: Citrate lays (ACL), NAD+ isocitrate dehydrogenase (NAD+ICDH), Glucose-6-phosphate (G6PD), and 6-phosphogluconate dehydrogenase (6PGD), all these enzymes show, activities till the end of cultivation time including ACL which is regarded the key enzyme to differentiate between the two species oleaginous and non oleaginous. So, there is no main reason to non oleaginicity for this fungus. A further experiment has been done using Polyacrylamide gel electrophoresis to identify ME isoforms. The result of Polyacrylamide gel electrophoresis shows multi isoforms (A, B, C, D & E), with low intensity of isoform E, the isoforms that may involve in lipid synthesis. We have now studied the biochemistry of A.niger grown under conditions designed to promote lipid accumulation and can now advance a coherent hypothesis to explain why A niger could not accumulate lipid more than 6%. So the absence of isoforme E is the main reason for non oleaginicity in A niger.